The The Effect of Using English TikTok Songs on Students’ Descriptive Vocabulary Mastery - Rini Nur Isnaeni; Farida, Alief Noor (UIBU, 2026)
In today’s technology driven society, English language learning must be continuously updated with modern and engaging media to support students’ vocabulary development. However, in the learning process, many students still experience difficulties in understanding and using English vocabulary, especially descriptive vocabulary used to describe people, such as adjectives and nouns. Therefore, this study aims to determine whether the use of English TikTok songs can help improve junior high school students’ mastery of descriptive vocabulary effectively. This study uses a pre-test and post-test design in a quasi-experimental form. The research subjects were junior high school students, and five English TikTok songs were used as learning media. Pre- and post-tests were used to measure students’ descriptive vocabulary mastery before and after learning using English TikTok songs. The data obtained were then analyzed using a paired sample t-test. The results showed a significant increase in students’ descriptive vocabulary mastery after learning using English TikTok songs, with an average increase of 10.07 points (p < 0.05). This indicates that English TikTok songs are effective in helping students understand and use adjectives. Students’ writing became longer, more detailed, and clearer than before the treatment.